Getting the Best out of Regional Integration: Some Thoughts for Rwanda - Laura Collinson; Jaime de Melo (Fondation pour les études et recherches sur le développement international (FERDI), 2011)
Rwanda has made much progress towards integrating into the world economy, with yearly export growth rates close to 20%. However, largely because of being landlocked, Rwanda is still isolated from many trading partners and, because of the low share of trade in GDP, exports do not contribute much to overall growth. In its Vision 2020, the GOR decided to push for the "Promotion of Regional Economic Integration and Cooperation". This paper argues that this was, and continues to be, the right strategy to pursue.
Keywords: F15; O24; O55; 330